2018
DOI: 10.1017/s0033291718001113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of digital CBT for insomnia to reduce depression across demographic groups: a randomized trial

Abstract: Results provide evidence that the wide dissemination of dCBT-I may effectively target both insomnia and comorbid depression across a wide spectrum of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 55 publications
9
87
0
3
Order By: Relevance
“…First and foremost, a wealth of evidence has demonstrated that dCBT for insomnia is reducing depressive symptomatology. This has been demonstrated by using dCBT for insomnia not only as an adjunct therapy [ 57 ], but also as stand-alone treatment in trials including participants with comorbid symptoms of insomnia and depression [ 41 , 55 , 59 ], independent of whether the treatment was fully automated or guided by healthcare professionals. The effects sizes are typically in the moderate-to-large range.…”
Section: Evidence For Dcbt For Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost, a wealth of evidence has demonstrated that dCBT for insomnia is reducing depressive symptomatology. This has been demonstrated by using dCBT for insomnia not only as an adjunct therapy [ 57 ], but also as stand-alone treatment in trials including participants with comorbid symptoms of insomnia and depression [ 41 , 55 , 59 ], independent of whether the treatment was fully automated or guided by healthcare professionals. The effects sizes are typically in the moderate-to-large range.…”
Section: Evidence For Dcbt For Insomniamentioning
confidence: 99%
“…This is however not unique to dCBT for insomnia; dCBT programs for other disorders have equal, or even larger, problems with attrition [ 74 ]. So far, it has proven difficult to find indicators of dropout; studies have suggested that a lower social economic status [ 55 ], a longer sleep duration, less severe insomnia complaints, and more depressive symptoms increase dropout [ 75 ].…”
Section: Evidence For Dcbt For Insomniamentioning
confidence: 99%
“…IPSRT-inspired approaches may be additionally beneficial in supporting individuals with BPD where such social rhythm instability is apparent. Furthermore, as maladaptive sleep cognitions are common in BPD (50) and this may further perpetuate the severity of insomnia, cognitive behaviour therapy for insomnia (CBT-I) could be used to address dysfunctional beliefs and behaviours about sleep which has been shown to mediate improvement of depression and psychological well-being (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Our benchmark for preliminary efficacy was at least 50% of participants demonstrating a clinically meaningful change in insomnia severity from baseline‐to‐posttreatment. The benchmark of 50% was selected based on previous studies reporting response rates between 39 and 65% after digital CBT‐I …”
Section: Methodsmentioning
confidence: 99%